Specific Turbulence- and Chaoborus-Induced Morphotypes Affect the Streamlining Properties of Daphnia cucullata - Horstmann, Martin; Weiss, Linda C.; Tollrian, Ralph (Frontiers in Ecology and Evolution, 2022)
Inducible defences are a wide-spread defensive mechanism in Daphnia. For example D. cucullata, is known to form different adaptive morphologies under changing environmental conditions. In this species, predator presence elicits defensive helmets. Defended animals perform better and survive more frequently in predation attempts. Another peculiarity of D. cucullata is that they develop these defences also in response to turbulence. The mechanisms that underly this defensive effect are so far unclear. Therefore, we investigated the three-dimensional morphology of the typical, the turbulence- and Chaoborus-exposed morph and analysed their surface and volume alterations. We furthermore measured the swimming velocities of these morphs. With the determined shapes and the measured velocities, we simulated the drag force under different angles of attack and determined the energy necessary to move through the water. In the light of previous findings and hypotheses we here discuss biomechanical mechanisms that improve D. cucullata’s fitness in the investigated environments.